2018
DOI: 10.1080/00131881.2018.1454263
|View full text |Cite
|
Sign up to set email alerts
|

The power of the word: students’ and school staff’s use of the established bullying definition

Abstract: Background: Previous research has found that bullying is often defined differently by students, staff and researchers, leading researchers to call for a more consistent use of the term in practice to enable better intervention and measurement. However, little is known about the consequences of a more consistent use of the term in school. Purpose: The article examines the consequences of schools adopting an exact definition of bullying. Sample: Twenty Norwegian primary and lower secondary schools were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
0
31
0
5
Order By: Relevance
“…Bullying may also fall under the staff radar due to a lack of awareness, even in cases where they are aware of the events that students may experience as bullying. Teachers may regard it as merely 'friendly teasing', as something students 'ought to put up with', or they may define what they see as a 'conflict', rather than bullying (Eriksen, 2018), and, therefore, not something that they are required to do anything about. The discrepancy may also be augmented by the way the questions are posed in the survey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bullying may also fall under the staff radar due to a lack of awareness, even in cases where they are aware of the events that students may experience as bullying. Teachers may regard it as merely 'friendly teasing', as something students 'ought to put up with', or they may define what they see as a 'conflict', rather than bullying (Eriksen, 2018), and, therefore, not something that they are required to do anything about. The discrepancy may also be augmented by the way the questions are posed in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy may also be augmented by the way the questions are posed in the survey. Whereas the students are asked about specific events and encounters, without the term 'bullying' being used, questions to staff use the term 'bullying', which is a word that for many educators is understood as being more restrictive and more serious -this may perhaps make them less willing to define actions as 'bullying', even if they are aware of them (Eriksen, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-teaching staff members' definitions of school bullying often differ from the definitions commonly used by researchers (Hazler, Miller, Carney, & Green, 2001); likewise, non-teaching staff' and students' definitions also tended to differ (Eriksen, 2018;Maunder, Harrop, & Tattersall. 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Results showed that adolescents' and adults' descriptions of school bullying were consistent in terms of defining indirect behaviors more likely than direct behaviors, https://doi.org/10.15405/epsbs.2019.11.1 Corresponding Author: Kristi Kõiv Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 4 however both adult samples defined the direct and indirect behaviors as bullying more frequently than pupils and perceived bullying behaviors as more serious than pupils. Eriksen (2018) conducted interviews among group of students and school staff (teachers, principals and school support staff) members by asking to define school bullying. Results reveal that school staff construed a rigid definition reflecting the power to decide how to follow their intervention practice and students used the term as a tool for social positioning.…”
Section: Introductionmentioning
confidence: 99%